Kedudukan Omnibus Law Dalam Sistem Perundang-Undangan Indonesia - Andi Desmon (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2021)
The idea of omnibus law as a method of drafting legislation in Indonesia has become a topic of discussion among law makers, both theoretical law bearers and practical law bearers. Based on the research, it can be said that the position of the omnibus law in the Indonesian legal system is included in the law and has the same degree as the law, which is made and implemented by the body that carries out the legislative function (DPR with the President), so it can be tested. by the constitutional court, both materially and formally examined.